Investment Risk & Uncertainty: A Practical Approach for Australian Companies. (Book). - Bruns, William J.; Istvan, Donald F. (The Accounting Review, 1969)
Reviews the book "Investment Risk & Uncertainty: A Practical Approach for Australian Companies," by P. Spry-Bailey.